2018
DOI: 10.1371/journal.ppat.1007283
|View full text |Cite
|
Sign up to set email alerts
|

Prions activate a p38 MAPK synaptotoxic signaling pathway

Abstract: Synaptic degeneration is one of the earliest pathological correlates of prion disease, and it is a major determinant of the progression of clinical symptoms. However, the cellular and molecular mechanisms underlying prion synaptotoxicity are poorly understood. Previously, we described an experimental system in which treatment of cultured hippocampal neurons with purified PrPSc, the infectious form of the prion protein, induces rapid retraction of dendritic spines, an effect that is entirely dependent on expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(74 citation statements)
references
References 103 publications
1
72
1
Order By: Relevance
“…S5). We have shown previously that Aβ oligomer toxicity in this assay is PrP C -dependent 50 . We found that toxicity was correlated with the size of aggregate; ADDLs and 3-day protofibrils induced more marked spine retraction than 7-day protofibrils, while fully polymerized fibrils were relatively inert.…”
Section: Localization Of Prp On Neurotoxic Aβ Assembliesmentioning
confidence: 60%
See 1 more Smart Citation
“…S5). We have shown previously that Aβ oligomer toxicity in this assay is PrP C -dependent 50 . We found that toxicity was correlated with the size of aggregate; ADDLs and 3-day protofibrils induced more marked spine retraction than 7-day protofibrils, while fully polymerized fibrils were relatively inert.…”
Section: Localization Of Prp On Neurotoxic Aβ Assembliesmentioning
confidence: 60%
“…PrP C also serves as a cell-surface receptor mediating the synaptotoxic activity of PrP Sc , the infectious form of PrP. However, our evidence indicates that the signaling pathways initiated by PrP Sc and Aβ may not be identical 50 .…”
Section: Discussionmentioning
confidence: 76%
“…B . A hippocampal neuronal culture system allows analysis of the acute toxic effects of prions on synaptic structure and function . Left: Neurons are isolated from hippocampi of neonatal pups and cultured at low density on coverslips that are suspended facedown, via wax dots, over a feeder layer of astrocytes.…”
Section: In Vitro Systems For Studying Prion Neurotoxicitymentioning
confidence: 99%
“…Treatment with purified PrP Sc , but not mock‐purified material, leads to retraction of dendritic spines, revealed by staining with fluorescent phalloidin, as well as local increases in p38 MAPK phosphorylation, visualized by staining with antibodies to phospho‐p38 (red) and total p38 (green). Electrophysiological abnormalities in synaptic transmission are also detectable using patch‐clamping techniques . Images of mice were taken from Servier Medical Art ( http://smart.servier.com).…”
Section: In Vitro Systems For Studying Prion Neurotoxicitymentioning
confidence: 99%
See 1 more Smart Citation